Penerapan Metode Tahsin dalam Pembelajaran Al-Quran di Mts Al-I’anah Kosambi Karawang - Camelia Permata Putri; Lilis Karyawati; Nia Karnia (Al-Munawwarah : Jurnal Pendidikan Islam, 2025)
This study will describe the process and results of learning the Qur'an through the tahsin method at Mts Al-I’anah Kosambi Karawang. through the tahsin method. While the learning outcomes of the Qur'an in question are describing the abilities of students before and after participating in learning the Qur'an through the tahsin method. This study aims to describe the process and results of learning the Qur'an through the tahsin method at the student Mts Al-I’anah Kosambi Karawang. This study uses a qualitative research approach with the research subjects are teachers and students who follow the learning of the Qur'an through the tahsin method. The data obtained came from the data extracted by the researcher through observation, interview and documentation techniques. While the data analysis uses the analytical model of Miles and Huberman, including data reduction, data presentation, and drawing conclusions. The results of this study indicate that the learning activities of the Qur'an through the tahsin method get a good response from the students. This has a positive impact on the development of students' ability to read the Qur'an from not fluent to fluent. The data is evidenced from the results of student tests before taking part in learning the Qur'an through the tahsin method, and data on the results of student tests after taking part in learning the Qur'an through the tahsin method within a period of one semester.